The analysis of gas dynamics equations with initial and boundary conditions and the construction of the corresponding averaged system - Krylovas, Aleksandras; Kriauzienė, Rima (Lietuvos matematikos rinkinys, 2013)
In this paper hyperbolic system of the first order gas dynamics PDE with initial and boundary conditions is studied. The aim of the paper is to construct the averaged system of differential equations in order to find the uniformly valid in a large domain asymptotical solution. The averaged system is a new object of asymptotical analysis.
Keywords: gas dynamics; acoustic waves; asymptotical analysis; averaging; hyperbolic systems